“Como no basquete e vôlei só 'servem' os altos, no futebol, só os machos”: experiências de um estudante gay durante a formação inicial em Educação Física - Santos, Rafael Silva dos (2023)
The Dissertation presented exposes as problematic a concern for analyzing experiences of a gay student during initial training in Physical Education. It is part of the Research Line “Educational Knowledge and Practices” of the Graduate Program in Education at the Federal University of Uberlândia. Concomitantly, through studies initiated in the Research Group Education, Sexualities and Performativities (GPESP), the general objective of this proposal is to analyze experiences that a gay student, from an undergraduate course in Physical Education, Bachelor's degree, from a private Education Institution Superior (IES) in a medium-sized city in the interior of the state of Goiás, experience during the initial training process. For this, we opted for a qualitative field research, with an exploratory character. In addition, for data production, we used a questionnaire with open and closed questions and a narrative interview as instruments. Since, in the perspective of searching in the field, situations experienced to be problematized, we analyzed narrative interviews, as these are a research instrument that explores not only loose and isolated speeches, they represent facts that build a life story, that help to build the identity of the subject and are the combination of experiences that contribute to formulate future stages of experiences. Accordingly, by means of semi-open questionnaires, with objective and subjective questions and a semi-structured interview, we tried to describe reports of the student's experiences in relation to the formulated general objective. As main results, we had no violence within the walls of Higher Education Institutions, however, personal resistance, strategy for coping with gayphobia and dreams of a better life were drivers for (re)existence. Furthermore, it is intended that this material reach repercussions of readings at different levels, and that it can be a direction for the conceptual problematization of other researchers.